A commentary on Quintus of Smyrna, "Posthomerica" 14 - Carvounis, Katerina (Oxford University Press, 2019)
The Posthomerica, a Greek epic by Quintus of Smyrna believed to have been written in the third century AD, tells the story of the Trojan War beginning with the events immediately following the end of the narrative of the Iliad. Valued as one of the few surviving detailed poetic accounts of this period, Book 14, the final book of the poem, covers the events that take place the day after the sack of Troy, from Helen's return to Menelaus and the sacrifice of Polyxena, to the homeward journey of the victorious Greeks, which is abruptly interrupted by a divine storm. 0This detailed commentary divides the text of Posthomerica 14 into smaller narrative units, introducing each with an overview of the relevant literary tradition and a discussion of Quintus' possible direct models. There follows a line-by-line commentary addressing points of literary, stylistic, lexicographic, and textual-critical interest, and providing readers with a range of notes on background and vocabulary. The aim throughout is to illuminate the main features of Quintus' poetry and to offer as full an interpretation as possible of Posthomerica 14 within its literary context and in dialogue with the earlier tradition, in particular the diction, motifs, and narrative and literary techniques of the Homeric poems and the epic tradition more generally. For readers new to the Posthomerica, the volume also includes a thorough and up-to-date introduction offering an accessible overview of the poem's content, dates, context, models, and possible sources, including both the Epic Cycle and Latin literature.
Aus dem Vorwort: "This book has evolved from my Oxford doctoral thesis, submitted as Aikaterini Nina Carvounis, 'Transformations of epic: reading Quintus of Smyrna, Posthomerica XIV' and awarded in 2005"
Keywords: Quintus -- Smyrnaeus -- ca. 4. Jh -- Posthomerica -- 14; Quintus / Smyrnaeus / active 4th century / Posthomerica; Trojan War / Poetry; Troy (Extinct city) / Poetry; Trojan War; Posthomerica (Quintus, Smyrnaeus); Poetry; Hochschulschrift; Kommentar